Metode Perbaikan Bacaan Yang Efektif untuk Pesantren Qur’an - Fajrianita, Noni; Maryedho, Furkan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to describe and determine the effectiveness of the tahsin learning method or improvement of reading the Qur'an using the Ottoman Adult method. This qualitative research uses a phenomenological approach. This research was carried out at the Al-Fida Islamic Islamic Boarding School Bengkulu, especially for the new female students for the 2021/2022 academic year. The research subjects consisted of the Coordinator of Brothers, Musyrifahs and Santriwati. Data collection techniques include observation, interviews, and documentation, data analysis techniques using an interactive model from Miles and Huberman where the analysis process is carried out simultaneously with the observation and interview processes as well as documentation. The results of the study, from 15 new female students as many as 80% or 12 children were able to complete tahsin in approximately 3 months and 20% or 3 female students completed within 5 months. The conclusion of the adult Ottoman method has a Tagline; Easy, Fast and Fun has been proven to be effective in teaching the correct reading of the Qur'an, both in theory and practice as a preparation for students before starting tahfidz. Other factors that play a role in the success of learning must be considered, such as competent teachers and the sincerity of the students in following all the learning processes. Keywords: Effectiveness, Adult Ottoman tahsin method, Qur'an Islamic Boarding School. amaan dengan proses observasi dan wawancara serta dokumentasi. Hasil penelitian, dari 15 santriwati baru sebanyak 80 % atau 12 orang anak mampu menuntaskan tahsin dalam waktu kurang lebih 3 bulan dan 20 % atau 3 orang santriwati tuntas dalam waktu 5 bulan. Simpulan metode Utsmani Dewasa memiliki Tagline : Mudah, Cepat dan Menyenangkan sudah terbukti efektif dalam mengajarkan bacaan Qur’an yang benar, baik secara teori dan prakteknya sebagai persiapan santri sebelum mulai tahfidz. Faktor-faktor lain yang berperan dalam kesuksesan pembelajaran harus diperhatikan, seperti guru yang kompeten dan kesungguhan santriwati mengikuti semua proses pembelajaran. Kata Kunci: Effektifitas, Metode tahsin Utsmani Dewasa, Pesantren Qur’an.